2018
DOI: 10.2147/opth.s163734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of ocular and systemic findings in diagnosed cases of abusive and non-abusive head trauma

Abstract: PurposeChild abuse is a leading cause of death in infants, which is often associated with abusive head trauma (AHT). The purpose of this retrospective analysis was to identify ocular and systemic findings in confirmed cases of AHT and compare them to a group of non-abusive head trauma (NAHT) patients.Patients and methodsA retrospective chart review of 165 patients with accidental and non-accidental trauma admitted between 2013 and 2015 to Children’s Hospital and Medical Center in Omaha, NE, USA, was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…[58][59][60] , Suh and associates showed that infants delivered vaginally without complication may present with RH up to 50% of the cases, but most of these cases have only preretinal and intraretinal hemorrhages in the posterior pole with no signs of retinoschisis and vitreous hemorrhage that can be associated with vitreoretinal separation. 50,51 Furthermore, most of these RHs resolved within a few weeks, although a few isolated cases lasted up to 3 months of age. 50,51 The present FE model may shed light on pathophysiology of the RH patterns and differentiating findings in AHT from other causes.…”
Section: Results Of the Computer Model Show That Shakingmentioning
confidence: 99%
See 1 more Smart Citation
“…[58][59][60] , Suh and associates showed that infants delivered vaginally without complication may present with RH up to 50% of the cases, but most of these cases have only preretinal and intraretinal hemorrhages in the posterior pole with no signs of retinoschisis and vitreous hemorrhage that can be associated with vitreoretinal separation. 50,51 Furthermore, most of these RHs resolved within a few weeks, although a few isolated cases lasted up to 3 months of age. 50,51 The present FE model may shed light on pathophysiology of the RH patterns and differentiating findings in AHT from other causes.…”
Section: Results Of the Computer Model Show That Shakingmentioning
confidence: 99%
“…In contrast to our model predictions for shaking, in cases of increased intracranial pressure with cerebral edema or compressive subdural hematoma, increases in retinal venous pressure and axoplasmic transport interference of ganglion cell layers can result in peripapillary hemorrhages localized to the posterior pole with mostly intraretinal hemorrhages. 46,[50][51][52][53][54][55][56][57] RH in AHT cases commonly show multilayered and diffuse RH involving the peripheral retina in addition to the macular area. [58][59][60] , Suh and associates showed that infants delivered vaginally without complication may present with RH up to 50% of the cases, but most of these cases have only preretinal and intraretinal hemorrhages in the posterior pole with no signs of retinoschisis and vitreous hemorrhage that can be associated with vitreoretinal separation.…”
Section: Results Of the Computer Model Show That Shakingmentioning
confidence: 99%
“…Retinal injuries were found to be highly specific for NAT in this study. Retinal injuries have historically been a hallmark of NAT, often due to sheering forces experienced in abusive head trauma [ 5 , 10 , 11 ]. Only one case of accidental trauma from a fall resulted in a retinal injury in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral injuries should still be flagged for suspicion of NAT because they were still present in 37.5% of the cases. In addition, abusive head trauma (AHT) has been shown in other studies to be one of the most common types of NAT and the most morbid and potentially fatal [ 4 , 5 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiblin [41] National study shows that abusive head trauma mortality in Sweden was at least 10 times lower than in other Western countries X X Morgan et al [42] Clinical comparison of ocular and systemic findings in diagnosed cases of abusive and non-abusive head trauma X X Gencturk et al [43] Various cranial and orbital imaging findings in pediatric abusive and non-abusive head trauma, and relation to outcomes X X Sidpra et al [44] Skull fractures in abusive head trauma: A single centre experience and review of the literature X Wright et al [45] Disability and visual outcomes following suspected abusive head trauma in children under 2 years X Donaldson et al [46] Ophthalmology referral as part of a multidisciplinary approach to suspected abusive head trauma X Payne et al [47] Recognition and nursing management of abusive head trauma in children X X…”
Section: Andersson Andmentioning
confidence: 99%